Malaria-Associated Anaemia: A Cross-Sectional Study in Mau Bokul Village, East Sumba - Lalel, Indah Christine; Deo, Dwita Anastasia; Setianingrum, Elisabeth Levina; Handoyo, Nicholas Edwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Malaria remains a major public health challenge in eastern Indonesian and anaemia is a principal haematological complication with notable clinical and functional consequences. Community-based data quantifying malaria-associated anaemia in East Sumba are scarce. This study aimed to determine the prevalence of anaemia associated with malaria and to evaluate the association between malaria infection and anaemia among residents of Mau Bokul Village, East Sumba. An analytical cross-sectional survey was conducted on 98 community participants recruited by consecutive sampling during June–July 2025. Malaria diagnosis was established by microscopy of Giemsa 3%-stained thick blood films and haemoglobin (Hb) was quantified using a point-of-care digital meter (Easy Touch GCHb). Fisher's Exact Test analyzed the association between malaria and anaemia with significance set at (p < 0.05). The results are indicate malaria prevalence was 8.2% (8/98), and anaemia prevalence was 34.7% (34/98). All malaria-positive individuals were anaemic. The association between malaria and anaemia was statistically significant (p < 0.001).